2021
DOI: 10.1038/s41467-021-20936-8
|View full text |Cite
|
Sign up to set email alerts
|

Mouse entorhinal cortex encodes a diverse repertoire of self-motion signals

Abstract: Neural circuits generate representations of the external world from multiple information streams. The navigation system provides an exceptional lens through which we may gain insights about how such computations are implemented. Neural circuits in the medial temporal lobe construct a map-like representation of space that supports navigation. This computation integrates multiple sensory cues, and, in addition, is thought to require cues related to the individual’s movement through the environment. Here, we iden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 59 publications
2
26
0
Order By: Relevance
“…The robust representation of vestibular stimuli observed here complements and extends recent work on vestibular-evoked responses in the rodent cortical network (44,62,67). AHV neurons in the RSP may belong to the same population of cells that were previously shown to provide head motion information to the primary visual cortex (44), and may also be the source of head motion signals in other cortical areas that are directly connected to the RSP, such as postsubiculum ( 68) and the entorhinal cortex (69). The pathways that provide AHV information to the RSP are yet to be described but one possible route could involve the ascending thalamocortical head direction network.…”
Section: Discussionsupporting
confidence: 79%
“…The robust representation of vestibular stimuli observed here complements and extends recent work on vestibular-evoked responses in the rodent cortical network (44,62,67). AHV neurons in the RSP may belong to the same population of cells that were previously shown to provide head motion information to the primary visual cortex (44), and may also be the source of head motion signals in other cortical areas that are directly connected to the RSP, such as postsubiculum ( 68) and the entorhinal cortex (69). The pathways that provide AHV information to the RSP are yet to be described but one possible route could involve the ascending thalamocortical head direction network.…”
Section: Discussionsupporting
confidence: 79%
“…Cortical AHV neurons that track the activity of the vestibular organs were first reported in head-fixed monkeys and cats decades ago (Büttner and Buettner, 1978;Vanni-Mercier and Magnin, 1982). Later, AHV neurons were also found in the rodent cortex, specifically in pre-and postsubiculum (Preston-Ferrer et al, 2016;Sharp, 1996), entorhinal cortex (Mallory et al, 2021), posterior parietal cortex (Wilber et al, 2014), anterior cingulate cortex (Mehlman et al, 2019) and RSC (Cho and Sharp, 2001). However, the underlying modalities that drive tuning have remained unknown.…”
Section: Discussionmentioning
confidence: 99%
“…To reduce the influence of conjunctive head direction tuning, we limited the range of directions that the mouse could face by rotating the stage back and forth between two target positions located 180°apart (Figure 3A, 4928 cells, 10 mice). To determine the distribution of behaviourally relevant AHV, we analysed published data of freely moving mice (Laurens et al, 2019) and found that about 90 % of all head rotations are slower than 180°/s (see Methods, n = 25 mice, see also Mallory et al (2021)). Therefore, we rotated the mice at speeds between -180 to +180°/s in steps of 45°/s (Figure 3A).…”
Section: A Large Fraction Of Turn-selective Neurons Encode Ahvmentioning
confidence: 99%
“…The location information is transmitted to the main computer on a dedicated link. Additional sensors include the nose-poke detectors at each feeding port that report their state in real time; the status of the food and water ports; and analog sensors carried by the animals such as a microphone, accelerometers, and gyroscopes 33 .…”
Section: The Setupmentioning
confidence: 99%